Optimización del consumo energético de los equipos de BES en el clúster A, de un campo de crudo pesado ubicado en la Cuenca de los Llanos Orientales. (2021)
Frontera Energy Corp can be categorized as one of the companies of Colombia with major investment in technology reefer to BES, this represents an important challenge when is related to the energetic system, due that it demands a considerable amount of electricity for its operation. For this reason, it is developed a study that proposes through simulation and field application, generating an optimization and economic saving referring to energy consumption, without operation over cost to produce oil.